Translation‐dependent mRNA cleavage by YhaV in Escherichia coli. Issue 13 (26th June 2017) - Choi, Wonho; Yamaguchi, Yoshihiro; Lee, Jae‐Woo; Jang, Kyung‐Min; Inouye, Masayori; Kim, Sung‐Gun; Yoon, Min‐Ho; Park, Jung‐Ho
Abstract : Many bacteria have toxin–antitoxin (TA) systems, where toxin gene expression inhibits their own cell growth. mRNA is one of the well‐known targets of the toxins in the type II toxin–antitoxin systems. Here, we examined the ribosome dependency of the endoribonuclease activity of YhaV, one of the toxins in type II TA systems, on mRNA in vitro and in vivo . A polysome profiling assay revealed that YhaV is bound to the 70S ribosomes and 50S ribosomal subunits. Moreover, we found that while YhaV cleaves ompF and lpp mRNAs in a translation‐dependent manner, they did not cleave the 5′ untranslated region in primer extension experiments. From these results, we conclude that YhaV is a ribosome‐dependent toxin that cleaves mRNA in a translation‐dependent manner. Abstract : Read the Commentary on this article at doi:10.1002/1873-3468.12715